Protective effect of bifidobacteria in an experimental model of Clostridium difficile associated colitis - Trejo, Fernando Miguel (2013)
The aim of this study was to evaluate the ability of Bifidobacterium strains to prevent the effects associated with Clostridium difficile infection in a hamster model of enterocolitis. After clindamycin treatment (30 mg/kg), animals were infected intragastrically with C. difficile (5 × 108 CFU per animal). Seven days prior to antibiotic administration, probiotic treatment was started by administering bacterial suspensions of bifidobacteria in drinking water. Strains CIDCA 531, CIDCA 5310, CIDCA 5316, CIDCA 5320, CIDCA 5323 and CIDCA 5325 were used. Treatment was continued during all the experimental period. Development of diarrhoea, enterocolitis and mortality were evaluated. All the infected animals belonging to the placebo group developed enterocolitis (5/5) and only two dead (2/5) whereas in the group administered with Bifidobacterium bifidum strain CIDCA 5310 the ratio of animals with enterocolitis or dead decreased significantly (1/5 and 0/5 respectively). Biological activity of caecum contents was evaluated in vitro on Vero cells. Animals treated with strain CIDCA 5310 presented lower biological activity than those belonging to the placebo group. The present study shows the potential of selected strains of bifidobacteria to antagonise, in vivo, the virulence of C. difficile.